Constitution of freedom : an introduction to legal constitutionalism - Sajó, András (OUP, 2017)
Sajó and Uitz's intellectual history of the constitutional ideal is rich in contextual detail and informed by case studies that give an overview of both the theory and practice of constitutionalism worldwide. Classic constitutions are contrasted with twentieth-century and contemporary endeavours, and experimentations in checks and balances. Their endeavour is neither apologetic (and certainly not celebratory), nor purely defensive: this book demonstrates why constitutionalism should continue to matter. Between the rise of populist, anti-constitutional sentiment and the normalization of the apparatus of counter-terrorism, it is imperative that the political communities who seek to sustain democracy as freedom understand the importance of constitutionalism. This book is essential reading for students of law and general readers without prior knowledge of the field, as well as those in politics who believe they know how government works. It shows what is at stake in the debate on constitutionalism.